Assessment of the Floristic Composition, Biological Spectrum, Leaf Size Spectra and Traditional Conservation Management of A Sacred Grove in West Midnapore District, West Bengal, India - Sen, Uday Kumar; Bhakat, Ram Kumar (Indian Forester, 2019)
Sacred grove is fine example of community based nature conservation without any external support. Various plants and animals that are threatened in the forest are well conserved within these patches. In this viewpoint, the present study was carried out to exploring the biological spectrum, leaf size spectra, conservation status, management and utilization of the existing vegetation of a sacred grove, namely Joypur Joysini Matar Than (JJMT) the West Midnapore district of West Bengal state in India. Floristic list of the study area revealed that the vegetation of JJMT was diverse and composed of 177 species belonging to 165 genera distributed in 59 families from 31 orders according to APG IV classification. The dominant order and family in terms of species richness were Lamiales (23 species) and Fabaceae (16 species) respectively. Biological spectrum showed the study area was classified as â€œtherochamaephyticâ€ type of phytoclimate. As regards the leaf size spectra, mesophyll (23.16%) was found to be higher than other leaf size classes. The study area being a sacred grove may be well protected by further understanding its importance to the ecosystem of the locality and its useful resources for the future as well.